Huang-Lian-Jie-Du Decoction Ameliorates Acute Ulcerative Colitis in Mice via Regulating NF-κB and Nrf2 Signaling Pathways and Enhancing Intestinal Barrier Function - Yuan, Ziwen; Yang, Lihong; Zhang, Xiaosong; Ji, Peng; Hua, Yongli; Wei, Yanming (Frontiers in Pharmacology, 2019)
Evidence shows that intestinal inflammation, oxidative stress and the injure of mucosal barrier are closely related to the pathogenesis of ulcerative colitis (UC). Huang-lian-Jie-du Decoction (HLJDD) is a well-known prescription of traditional Chinese medicine with anti-inflammatory and antioxidative activities, which may be used to treat UC. However, its therapeutic effect and mechanism are still unclear. In this study, the UC model of BABL/c mice were established by DSS [3.5% (w/v)], and HLJDD was given orally for treatment at the same time. During the experiment, the clinical symptoms of mice were scored by disease activity index (DAI). Besides, the effects of HLJDD on immune function, oxidative stress, colon NF-κB and Nrf2 signaling pathway and intestinal mucosal barrier function in UC mice were also investigated. The results showed that HLJDD could alleviate body weight loss and DAI score of UC mice, inhibit colonic shortening and relieve colonic pathological damage, and reduce plasma and colon MPO levels. In addition, HLJDD treatment significantly up-regulated plasma IL-10, down-regulated TNF-α and IL-1β levels, and inhibited the expression of NF-κB p65, p-IκKα/β and p-IκBα proteins in the colon. Moreover, NO and MDA levels in colon tissues were significantly reduced after HLJDD treatment, while GSH, SOD levels and Nrf2, Keap1 protein expression levels were remarkably elevated. Additionally, HLJDD also protected intestinal mucosa by increasing the secretion of mucin and the expression of ZO-1 and occludin in colonic mucosa. These results indicate that HLJDD could effectively alleviate DSS-induced mice UC by suppressing NF-κB signaling pathway, activating Nrf2 signaling pathway and enhancing intestinal barrier function.